Efektifitas Pembentukan Daerah Berdasarkan UU No 8 Tahun 2023 Guna Mendukung Otonomi Daerah Di Indonesia - Septian Arjuanda Putra Simatupang; Irna Sri Talenta; Helen Meliana R Hutajulu; Rizkika Kartadinata Siahaan; Sri Hadiningrum (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research examines the effectiveness of regional formation based on Law Number 8 of 2023 in order to support regional autonomy in Indonesia. The phenomenon of large-scale regional formation is quite worrying considering that many proposals are colored by the self-interest of the local elites who support them. Regional formation has only become a commodity of